Discovery of a Unique Clp Component, ClpF, in Chloroplasts: A Proposed Binary ClpF-ClpS1 Adaptor Complex Functions in Substrate Recognition and Delivery. Issue 10 (29th September 2015) - Nishimura, Kenji; Apitz, Janina; Friso, Giulia; Kim, Jitae; Ponnala, Lalit; Grimm, Bernhard; van Wijk, Klaas J.
Abstract : Discovery of a multimeric adaptor system for the chloroplast Clp protease machinery suggests a complex mechanism regulates substrate recognition and delivery in chloroplasts. Abstract: Clp proteases are found in prokaryotes, mitochondria, and plastids where they play crucial roles in maintaining protein homeostasis (proteostasis). The plant plastid Clp machinery comprises a hetero-oligomeric ClpPRT proteolytic core, ATP-dependent chaperones ClpC and ClpD, and an adaptor protein, ClpS1. ClpS1 selects substrates to the ClpPR protease-ClpC chaperone complex for degradation, but the underlying substrate recognition and delivery mechanisms are currently unclear. Here, we characterize a ClpS1-interacting protein in Arabidopsis thaliana, ClpF, which can interact with the Clp substrate glutamyl-tRNA reductase. ClpF and ClpS1 mutually stimulate their association with ClpC. ClpF, which is only found in photosynthetic eukaryotes, contains bacterial uvrB/C and YccV protein domains and a unique N-terminal domain. We propose a testable model in which ClpS1 and ClpF form a binary adaptor for selective substrate recognition and delivery to ClpC, reflecting an evolutionary adaptation of the Clp system to the plastid proteome.